Can the opening of high-speed rail promote household multidimensional relative poverty alleviation? - Hu Yaning; Lu Haiyan; Chai Hao; Gao Xinyang (Journal of Transport Geography, 2025)
Addressing poverty is paramount, aligning with the first Sustainable Development Goal focused on eradicating poverty in all its forms. While the effects of high-speed rail (HSR) on absolute poverty have been documented, its impact on relative poverty remains understudied. This paper examines the influence of HSR on household relative poverty in China through a quasi-experimental design. The main results are as follows: (1) The opening of HSR significantly reduced the household relative poverty by approximately 1.8 %. (2) This alleviation effect primarily transpires through the expansion of economic activities and employment opportunities. (3) Notably, the impact of HSR is more pronounced in lower-ranked, smaller cities and in the western regions of China. Moreover, households with migrant workers or those engaged in non-agricultural sectors derive greater benefits from HSR developments. Our results suggest that HSR opening could have contributed to China’s relative poverty alleviation. Policymakers can consider the role of transportation infrastructure in mitigating household relative poverty, especially for low rank cities, small cities and periphery regions in other developing countries.